2008
DOI: 10.1007/s11738-008-0215-x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular analyses of seedlings of two Tunisian durum wheat (Triticum turgidum L. subsp. Durum [Desf.]) varieties showing contrasting tolerance to salt stress

Abstract: Salinity is one of the severest environmental stresses affecting plant productivity. In many plant species, salt sensitivity is associated with the accumulation of sodium (Na ? ) in photosynthetic tissues. Here, we provide the physiological and molecular analyses of seedlings of two Tunisian durum wheat genotypes (Triticum turgidum L. subsp. Durum [Desf.]), Mahmoudi (salt sensitive) and Om Rabia3 (salt tolerant). Na ? and K ? contents in leaf sheath from Om Rabia3 were significantly higher than those of Mahmou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…This might be due to inhibition of germination by the high salts concentration of seaweed saps. Salt stress induced inhibition of seed germination, seedling growth and metabolic processes were reported in maize (Azevedo et al, 2004) and wheat (Brini et al, 2009), which corroborated the results of the present study. These results are in agreement with the findings of Gaurav Kumar and Dinabandhu Sahoo (2011).…”
Section: Germination Percentagesupporting
confidence: 93%
“…This might be due to inhibition of germination by the high salts concentration of seaweed saps. Salt stress induced inhibition of seed germination, seedling growth and metabolic processes were reported in maize (Azevedo et al, 2004) and wheat (Brini et al, 2009), which corroborated the results of the present study. These results are in agreement with the findings of Gaurav Kumar and Dinabandhu Sahoo (2011).…”
Section: Germination Percentagesupporting
confidence: 93%
“…Rawat et al (2011) observed a decrease in the germination rate of T. aestivum caryopses in soil with a salt concentration of 0-60 mM, while Hu et al (2012) noted this effect at FW fresh weight, DW dry weight, RWC relative water content 0-200 mM of NaCl. Brini et al (2009) found a significant decrease of caryopses germination of durum wheat under 200 mM of NaCl treatment. It is very interesting that germination ability in salt solutions is negatively correlated with seedling growth.…”
Section: Discussionmentioning
confidence: 84%
“…In some regions of the world, low annual precipitation necessitates irrigation of crop plants with water which sometimes could not be completely desalted. However, in most cases soil salinity is an effect of salt accumulation over long cultivation periods and deforestation (Brini et al 2009). In Poland, located in Central Europe, the progressive reduction of the groundwater level and more frequent periods of drought cause 30 % losses of grain yield, which results in the need for plant watering (Schar et al 2004;Martyniak et al 2007;Walter et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, the physiological analysis of the two Tunisian durum wheat genotypes showed differential tolerance to salinity (Brini et al, 2009). However, data concerning the effects of salinity on ROS production and antioxidant defense system in these two durum wheat cultivars are still lacking.…”
Section: Introductionmentioning
confidence: 94%
“…durum), Mahmoudi (salt sensitive) and Om Rabia3 (salt tolerant) were sterilized and then germinated on Petri dishes as described by Brini et al (2009). Three-day-old seedlings were transferred to containers with modified half-strength Hoagland's solution (Epstein, 1972).…”
Section: Plant Material Stress Conditions and Dry Weight Determinationmentioning
confidence: 99%